The Meaning of The Word “Sufaha’” In the Qur’an - Agus Yasin; Muhammad Muhammad (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The meaning of the Qur’an is knowledge of the interpretation of the Qur’anic verses, their reasons, and their syntax. Indeed, the meaning in the Qur’an is very broad there is a relationship between words and meanings. This study aims to reveal simantic meaning of the word “Sufaha’” in the Qur’an. In collecting data, researchers used the methode of documentation. That is by examining the basic meaning and context of the word. An important conclusion from this research is to explore in depth the meaning of the word “sufaha’” in the Qur’an and some of the hadith, the opinions of scholars, and words that have a close meaning to ‘suhafa’”. Based on the results of research that has been carried out by researchers, it is hoped that every reader, especially those who make the Qur’an their main study, pay attention to every word in the Qur’an with a semantic perspective. And to all readers to pay more attention to every meaning in the verses of the Qur’an so that they can understand the content in the verses of the Qur’an and avoid misunderstanding in interpreting them.